PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS COOPERATIVE LEARNING TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) SUB POKOK BAHASAN LUAS PERMUKAAN DAN VOLUME TABUNG DAN KERUCUT UNTUK SMP KELAS IX - Nurhadiyanti, Kiki; Sugiarti, Titik; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2015)
Abstract. The research aims to know the process and result of the development of mathematics learning materials based on Cooperative Learning of Team Assisted Individualization (TAI) type for surface wide and volume of cylinder and cone topic at ninth grade of junior high schooL. The purpose of Cooperative Learning of Team Assisted Individualization (TAI) type is to improve students ability in understanding mathematic problem solving. Learning materials development model refers to 4D Thiagarajan models which has 4 steps namely define, design, develop, and disseminate. This research has three products namely lesson plan, worksheet, and evaluation test. Based on validation process and tryout, the result shows that the coefficient of validity reachs 3 point, the percentages of teacher’s activities, students’ activities, and students’ responses are above 80%, it can be concluded that the learning instruments had fullfiled the validity, practice, and effective criteria. Key Words: 4D Thiagarajan models, Cooperative Learning of Team Assisted Individualization (TAI) type, surface wide and volume, cylinder and cone.